2014
DOI: 10.1186/1479-5876-12-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum, EDTA plasma and P100 plasma for luminex-based biomarker multiplex assays in patients with chronic obstructive pulmonary disease in the SPIROMICS study

Abstract: BackgroundAs a part of the longitudinal Chronic Obstructive Pulmonary Disease (COPD) study, Subpopulations and Intermediate Outcome Measures in COPD study (SPIROMICS), blood samples are being collected from 3200 subjects with the goal of identifying blood biomarkers for sub-phenotyping patients and predicting disease progression. To determine the most reliable sample type for measuring specific blood analytes in the cohort, a pilot study was performed from a subset of 24 subjects comparing serum, Ethylenediami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“…Protein biomarker discovery studies in blood‐derived samples generally rely on findings revealed in one blood preparation type by screening a sample cohort from a single collection site. Yet, as demonstrated previously (Schwenk et al , ; Qundos et al , ; O'Neal et al , ) and in the presented study, different blood preparation types cause proteins to be detected differentially. Furthermore, despite the use of standardized sample collection, handling and storage protocols, it is difficult to retain identical conditions at and during transport from different clinical sites, where even subtle fluctuations might cause variations in the downstream analysis.…”
Section: Discussionsupporting
confidence: 81%
“…Protein biomarker discovery studies in blood‐derived samples generally rely on findings revealed in one blood preparation type by screening a sample cohort from a single collection site. Yet, as demonstrated previously (Schwenk et al , ; Qundos et al , ; O'Neal et al , ) and in the presented study, different blood preparation types cause proteins to be detected differentially. Furthermore, despite the use of standardized sample collection, handling and storage protocols, it is difficult to retain identical conditions at and during transport from different clinical sites, where even subtle fluctuations might cause variations in the downstream analysis.…”
Section: Discussionsupporting
confidence: 81%
“…Changing between serum and plasma has been suggested to affect cytokine measurements [40,41], including measurements of IL-16, which is shown to yield lower levels in serum compared to plasma [42]. This lower yield was consistent in our study, where the medians of both the control group and the HIE group were lower compared to the original study.…”
Section: Discussionsupporting
confidence: 77%
“…Concerns have been raised regarding the reliability of immunological measurements using serum samples because of platelet activation and degranulation that consequently may alter the cytokine concentrations (O'Neal et al. ).…”
Section: Methodsmentioning
confidence: 99%